TAMBAK KARANG IN THE ERAU TRADITION AS A MEDIUM FOR CULTURAL VALUES EDUCATION IN KUTAI KARTANEGARA, EAST KALIMANTAN - Mardiana; Agus Cahyono; Widodo (RADJA PUBLIKA, 2026)
This study aims to examine the symbolic meanings of Tambak Karang within the Erau tradition of Kutai Kartanegara, identify the cultural values embedded in its form and use, and explore its role as a medium for cultural education among younger generations. The research employed a qualitative case study design. Data were collected through in-depth interviews with cultural practitioners and community elders, direct observation of the Erau ritual process, and documentation of visual and written sources related to Tambak Karang. The collected data were analyzed using thematic analysis supported by symbolic interpretation theory to reveal cultural messages reflected in the motifs, production process, and ritual function of Tambak Karang. The findings indicate that Tambak Karang embodies key cultural values, including responsibility, respect for ancestors, spirituality, creativity, cooperation, social awareness, harmony, and appreciation of local heritage. These values are expressed through visual symbols, ritual practices, and intergenerational knowledge transmission. In addition, Tambak Karang has been utilized as supporting learning material in art, culture, and history education in several schools. The study highlights the importance of Tambak Karang as a cultural educational medium that supports character formation, strengthens cultural identity, and contributes to the preservation of local traditions amid the pressures of globalization.